Specific high-resolution scheme to improve understanding of the spatio-temporal dispersion of lymphogranuloma venereum epidemic - Martínez-García, Laura; González-Alba, José María; Puerta, Teresa; Comunión, Alicia; Rodríguez-Jiménez, María Concepción; Orviz, Eva; Sánchez-Conde, Matilde; Rodríguez-Domínguez, Mario; Cantón, Rafael; Galán, Juan Carlos (Frontiers in Microbiology, 2022)
Lymphogranuloma venereum (LGV) is already endemic in vulnerable populations in several European countries, but more accurate molecular epidemiology data is necessary if we want to improve our understanding of the LGV epidemic in these countries. Current strategies to study the molecular epidemiology of LGV cases are schemes based on a few genetic fragments of Chlamydia trachomatis, which have demonstrated limited discriminatory power for LGV. The aim of this study was to propose a new combination of molecular markers, based on the most variable genes of L-genotypes genomes, for improving the characterization of the current LGV epidemic in Madrid (Spain). Four genes were selected according to diversity index (CTLon_0054, CTLon_0087, CTLon_0243 and CTLon_0301) for use in combination with ompA. In silico and experimental studies were performed to compare the previously described MLST schemes and our proposal. Moreover, the proposed scheme was applied (n=68) to analyse the spatio-temporal spread of the LGV cases. When using the MLST proposed by Klint et al. only a single ST was identified. However, the new proposal identified higher diversity, allowing the identification of three main groups. The temporal analysis showed that the major cluster was progressively diversifying, revealing a very active transmission chain. Furthermore, an L2b genome identical to that of the origin of the epidemic was detected, which suggests re-introductions or low screening rate in vulnerable populations. The spatial distribution suggests that the selection and spread of new variants takes place from the central district to the peripheral regions. This study about molecular epidemiology of LGV shows for the first time a spatio-temporal spread that increases our understanding and identifies areas with special susceptibility for maintenance of the endemic situation.